Incidental Zenker’s Diverticulum During Thyroid Surgery : A Rare Challenge - Punithamalar, Krishnan; Lu Tong, Lim; Hanzali, Jumastapha (Springer Nature, 2025)
This paper discusses the rare intraoperative finding of Zenker’s diverticulum (ZD) during thyroid surgery. While only two cases of incidental ZD during neck surgery have been previously reported, this discussion presents a third case discovered during a hemithyroidectomy. The complexities of managing such an incidental finding are highlighted, particularly given the lack of preoperative imaging confirmation and potential for complications. The importance of considering ZD as a differential diagnosis for patients presenting with dysphagia, even in the presence of thyroid nodules, is emphasized. Postoperative imaging, particularly fluoroscopic contrast swallow studies, is crucial for confirming the diagnosis. The paper outlines various surgical management options for ZD and the need for heightened awareness and careful consideration of incidental ZD during thyroid surgery to ensure optimal patient outcomes.